2015
DOI: 10.1371/journal.pone.0122241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unfermented and Fermented Whole Grain Rye Crisp Breads Served as Part of a Standardized Breakfast, on Appetite and Postprandial Glucose and Insulin Responses: A Randomized Cross-over Trial

Abstract: BackgroundWhole grain rye products have been shown to increase satiety and elicit lower postprandial insulin response without a corresponding change in glucose response compared with soft refined wheat bread. The underlying mechanisms for these effects have not been fully determined The primary aim of the study was to investigate if whole grain rye crisp bread compared to refined wheat crisp bread, elected beneficial effects on appetite and postprandial insulin response, similarly as for other rye products.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 67 publications
4
53
2
2
Order By: Relevance
“…To date, there are many controlled trials that directly investigated the effects of whole-grain interventions on putative intermediate biomarkers. [9,37] For example, results from a clinical trial in North Europe suggested that a greater proportion of whole grain rye in a Nordic diet is associated with favorable outcomes in LDL-cholesterol and log triglyceride concentrations. [9] A randomized cross-over trial suggested that consumption of unfermented and fermented whole grain rye crisp bread led to lower postprandial glucose and insulin response compared with refined wheat crisp bread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are many controlled trials that directly investigated the effects of whole-grain interventions on putative intermediate biomarkers. [9,37] For example, results from a clinical trial in North Europe suggested that a greater proportion of whole grain rye in a Nordic diet is associated with favorable outcomes in LDL-cholesterol and log triglyceride concentrations. [9] A randomized cross-over trial suggested that consumption of unfermented and fermented whole grain rye crisp bread led to lower postprandial glucose and insulin response compared with refined wheat crisp bread.…”
Section: Discussionmentioning
confidence: 99%
“…[9] A randomized cross-over trial suggested that consumption of unfermented and fermented whole grain rye crisp bread led to lower postprandial glucose and insulin response compared with refined wheat crisp bread. [37] All such clinical trials recruited small numbers of participants and were of short-term duration (<1 year). In addition, participants always consumed controlled portions of the foods, but not mimic ordinary daily consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-grain rye food products that are naturally rich in dietary fibre, such as porridge, soft bread and crisp bread, have consistently shown appetite-suppressing effects in human studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) .…”
mentioning
confidence: 99%
“…Clinical trials have suggested that consumption of whole grains may positively affect risk factors for CVD and cancer, including hypertension ( 31 , 32 ) , weight gain/obesity ( 4 , 5 , 33 , 34 ) , total and LDL-cholesterol ( 35 , 36 ) and type 2 DM ( 6 , 7 , 37 , 38 ) . For instance, Magnusdottir et al .…”
Section: Discussionmentioning
confidence: 99%